Hydraulic-Mechanical Coupling Model with Dual-Porosity Dual-Permeability for Anisotropy Coal Seams and Its Application in Mine Gas Extraction. (5th August 2019) - Huo, Bingjie; Jing, Xuedong; He, Aiping; Fan, Chaojun
Abstract : The parameters of pore-fracture structure and permeability have a controlling effect on the behaviors of gas adsorption/desorption and transportation in coal reservoir. A mathematic model for coal seams is of great significance to evaluate the mass migration within the coal fracture-matrix system. In this paper, the hydraulic-mechanical coupling model considering both dual-porosity dual-permeability and anisotropy characteristics is first established by using the methods of theoretical analysis, nuclear magnetic resonance (NMR) test, and numerical simulation. Then, this model is applied to simulate the gas migration characteristics of No. 3 coal seam in Changping Mine, China. Results show that the pore structure of No. 3 coal seam is characterized by small radius of pores and pore throats, which is determined by the NMR test, verifying the dual-permeability dual-porosity of coal seams. Both matrix permeability and fracture permeability increase approximately linearly with the process of mine gas extraction. The increased magnitude of the matrix permeability is greater than that of the fracture permeability. The permeability is inversely proportional to the anisotropy coefficient. The pressure gradient within the coal matrix and fracture increases first and then decreases with the extraction time. This pressure gradient is proportional to the anisotropy coefficient at the early stage of extraction and is inversely proportional to the anisotropy coefficient at the later stage. The seepage and diffusion flux are proportional to the anisotropy coefficient. The proportion of matrix-to-fracture seepage flux to the total flux increases first and then decreases to a certain value. The proposed model provides a guide for accurate designation of gas extraction from coal seams.